Richard Sennett, The Corrosion of Character. The personal consequences of work in the new capitalism - Κ. Η. (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]